Facile Hydrothermal Synthesis of Sn‐Mn Mixed Oxide Nano‐rods with Exposed (110) Facets and Remarkable Catalytic Performance. Issue 22 (4th August 2017) - Peng, Honggen; Zhang, Li; Sun, Qi; Shen, Jiating; Xu, Xianglan; Fang, Xiuzhong; Liu, Wenming; Wang, Zheng; Zhang, Ning; Wang, Xiang
Abstract: Metal oxides with special exposed facets have very important effect on their catalytic performances. Though mono‐metal oxides exposed special facets can be easily prepared via various approaches, the synthesis of mixed metal oxides exposed special facets are still a challenge to date. Herein, Sn−Mn mixed oxide nano‐rods exposed (110) facet have been successfully synthesized by a facile one step hydrothermal method firstly. The structure of Sn−Mn mixed metal oxide nano‐rods was confirmed by transmission electron microscopy (TEM), energy dispersive X‐Ray spectroscopy (EDX)‐mapping and the powder X‐ray diffraction (XRD) techniques. With the Sn−Mn molar ratios changed from 10–0 to 7–3, the morphology of the samples also changed simultaneously. Interestingly, with increasing the amount of Mn, the diameter of the nano‐rods was decreased evidently. On the other hand, when the Sn−Mn molar ratio was below 8–2 (assigned as SnMn8‐2 NR), the nano‐particles with irregular morphology were beginning occurred. All of the SnMn mixed oxides nano‐rods were shown improved catalytic performance for CO oxidation compared with pure SnO2 nano‐rods and MnOx nano‐particles. The superior catalytic performance of SnMn nano‐rods should be attributed to their special exposed (110) facet and more amount of surface active O species. It is noted that SnMn8‐2 NR is the most active catalyst among all these samples and have a good stability in the presence or absence of water vapor. This work can help people to design new kinds of mixed metal oxide catalysts with exposed facets. Abstract : Solid Solution Rods: Though mono‐metal oxides exposed special facets can be easily prepared via various approaches, the synthesis of mixed metal oxides exposed special facets are still a challenge to date. In this work, Sn−Mn mixed oxide nano‐rods exposed (110) facet have been successfully synthesized by a facile one step hydrothermal method for the first time and showed superior CO catalytic oxidation performance.